2007
DOI: 10.1007/s11154-007-9063-z
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly: Re-thinking the cancer risk

Abstract: Acromegaly is characterized by sustained elevation of circulating growth hormone (GH) and insulin-like growth factor I (IGF-I), and is clearly associated with increased morbidity and overall mortality mainly due to cardiovascular, metabolic, and respiratory diseases. Although cancer-related mortality varies widely amongst retroperspective studies, it appears to be consistently elevated mainly in patients with uncontrolled disease. We review individual tumor types including neoplasms of the colon, breast, prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 186 publications
(187 reference statements)
6
92
0
4
Order By: Relevance
“…Acromegaly is accompanied by organomegaly, metabolic deterioration, comorbidities, and increased mortality (4). Neoplasms are often found, but their incidence is controversial (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acromegaly is accompanied by organomegaly, metabolic deterioration, comorbidities, and increased mortality (4). Neoplasms are often found, but their incidence is controversial (6).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I acts by means of two mechanisms: increasing proliferation and reducing apoptosis. It was demonstrated that IGF-I increases proliferation of porcine thyroid cells and FRTL-5 rat thyroid cells, and potentiates TSH-mediated thyroid cell proliferation (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). In physiological conditions, thyroid follicular cells express IGF-I receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Most authorities now accept that patients with acromegaly have an increased risk of colorectal neoplasia, even if the exact degree of risk remains uncertain (18,(21)(22)(23)(24)(25)(26)(27). In the non-acromegalic population, the majority of colonic cancers develop from pre-malignant colonic adenomas, and several studies have demonstrated that colonoscopic screening and removal of adenomas reduce the incidence of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed an association between high circulating IGF-I and IGF-II concentrations and increased risk of colorectal cancer (6,7). Acromegalic patients whose hypersecretion of growth hormone is accompanied by elevated IGF-I levels have an elevated incidence of colorectal adenomas and cancer (8,9). These epidemiologic data are supported by an in vivo study in the mouse showing genetically deleted IGF-I expression in the liver, which reduced the circulating IGF-I concentration by 75% and delayed the growth of an orthotopic xenograft.…”
Section: Introductionmentioning
confidence: 99%